A comunidade e dieta de pequenos mamíferos em uma área de caatinga no Alto Sertão Sergipano - Hirakuri, Valter Levino (2013)
Considering the habitat influence in the occurrence of animal species and feeding ecology as a key factor on community dynamics, the relationship between habitat components and species richness and the abundance of small mammals community were evaluated, as well as the diet characterization of these species at Caatinga‟s area in Sergipe, Brazil. The capture-mark-recapture (CMR) method was applied at the Grota do Angico Natural Monument (MNGA), 100 Sherman‟s® traps were arranged in four sites (dense hiperxerophytic Caatinga) from July 2012 to February 2013. Monthly, the habitat variables and invertebrates availability were measured. Fecal samples were collected for food items identification. Twenty-four individuals belonging to three species, two marsupials (Gracilinanus agilis, N = 17 and Didelphis al-biventris, N = 1) and one rodent (Wiedomys pyrrhorhinus, N = 6) were captured, the recapture rate was 25%. The richness found was lower than other studies described in this biome. High habitat similarity were observed between the study sites, due to the high amount of litter, and the differences among them were influenced by components such as rock, cactus and brome-liads. The only habitat variable that positively influenced the abundance of G. agilis was the amount of bromeliads, there was no such relationship with W. pyrrhorhinus. Thirty seven fecal samples were collected, nine of W. pyrrhorhinus (all male samples) and 28 of G. agilis (11 female samples and 17 male samples). In these two species intake sample were identified eight invertebrates orders (Hymenoptera, Coleoptera, Hemiptera, Lepidoptera, Blattodea, Or-thoptera, Isoptera e Araneae), pulp and seeds were also registered. This is the first study on the feeding habits of W. pyrrhorhinus and G. agilis in Caatinga‟s biome . The two species showed high rates of arthropods intake and the diet composition of marsupial was similar to others studies in Cerrado biome, although in this study the proportions of consumption were higher. There were two food items new records‟ to G. agilis: Blattodea and Pilosocereus gou-nellei (Cactaceae) seeds. No difference was found between the sexes in the diet of G. agilis, however largest consumer of Hymenoptera by males and Orthoptera by females. Besides this study showed that marsupial has opportunistic feeding habits, consuming the more available arthropods orders in the environment.